Geographical cline and inter‐seaside difference in cone characteristics related to climatic conditions of old planted Pinus thunbergii populations throughout Japan. Issue 2 (19th December 2020) - Iwaizumi, Masakazu G.; Matsunaga, Koji; Iki, Taiichi; Yamanobe, Taro; Hirao, Tomonori; Watanabe, Atsushi
Abstract: Although cone morphology has been mainly utilized for taxonomy or forestry purposes, characterization of the environmental factors that influence its variation is still insufficient. Major conifers distributed over diverse climatic conditions like the Japanese archipelago could show cone morphology variation among populations related to large differences in key influential factors such as temperature, snow, irradiance and sunshine. Geographical variation in cone characteristics (cone size, seed production, seed productivity per cone and seed size) was examined across the species distribution in 24 old planted Pinus thunbergii populations (479 trees) along two major seasides in Japan (Pacific Ocean side and Japan Sea side). Variance components of cone characteristics explained by seaside were at similar levels to those for populations nested within seasides. Populations on the Japan Sea side produced cones that had larger size (length and width), higher seed production (number of filled seeds per cone and seed mass per cone) and seed productivity per cone (seed‐to‐ovule ratio). Analysis of covariance showed that significant latitudinal clines observed in cone size and seed productivity per cone were mostly a result of inter‐seaside differences. Linear mixed model analysis detected that geographical variation in cone size, seed production and seed productivity per cone in the populations were affected significantly by low temperature, more snow, less solar irradiance and less sunshine time. Large cone sizes and high seed productivity per cone found in the populations on the Japan Sea side could be explained by a genetic or plastic response to maintain reproductive success. Abstract : Geographical variation in cone characteristics was examined in 24 old planted Pinus thunbergii populations. Populations on the Japan Sea side produced cones that had larger size (length and width), higher seed production (number of filled seeds per cone and seed mass per cone) and seed productivity per cone (seed‐to‐ovule ratio). Linear mixed model analysis detected that geographical variation in cone size, seed production and seed productivity per cone in the populations was affected significantly by low temperature, more snow, less solar irradiance and less sunshine time. Large cone sizes and high seed productivity per cone found in the populations on the Japan Sea side could be explained by a genetic or plastic response to maintain reproductive success.